Challenge and Implementation of Content-Centric Networking - Xinggong Zhang; Tong Niu; Zongming Guo (Dianxin kexue, 2013)
CCN is communication architecture that takes content as a primitive,and retrieves content by name,not by host IP again.It builds on publish/subscribe and network-embedded caching with bandwidth-storage tradeoff.Since it is a clean-slate design,there are many issues to be explored.The concepts,characteristics,network model and recent advances of CCN were introduced.The challenges and some key issues CCN faced were also emphasized.In order to demonstrate the feasibility and implementations,two CCN system samples were also presented.